2014
DOI: 10.1016/j.clay.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of halloysite-water nanofluid for heat transfer applications

Abstract: Versión / Versió:Postprint Nanofluids based on water with halloysite (Hal) nanotubes were prepared and characterized in order to evaluate its suitability to be used as a heat transfer fluid. A characterization of the Hal powder nanoparticles was performed by means of SEM, TEM, WAXS, FTIR and TGA so that chemical composition, size and shape were determined. Stability of nanofluids was analyzed by means of zeta potential and light transmission measurements. Thermal conductivity, specific heat and viscosity of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
1
8
1
Order By: Relevance
“…In the pH value of 7.0~10.0, the Zeta potential of all of the samples tend to be in the range −60~−45 mV, especially the samples Hal-LF, Hal-CX, and Hal-TL, which were similar to previous results [6,15]. There is a slight increase at pH = 8, which can be attributed to the interior aluminoxane surface (IEP 9) [48]. The largest negative potential (−62.0 mV) was detected at pH = 11.0 on the Hal-AU sample.…”
Section: Zeta Potential Analysissupporting
confidence: 79%
See 1 more Smart Citation
“…In the pH value of 7.0~10.0, the Zeta potential of all of the samples tend to be in the range −60~−45 mV, especially the samples Hal-LF, Hal-CX, and Hal-TL, which were similar to previous results [6,15]. There is a slight increase at pH = 8, which can be attributed to the interior aluminoxane surface (IEP 9) [48]. The largest negative potential (−62.0 mV) was detected at pH = 11.0 on the Hal-AU sample.…”
Section: Zeta Potential Analysissupporting
confidence: 79%
“…Many typical vibration bands can be found on IR spectra of different clay minerals, while the spectra of halloysite in the range 550~1350 cm −1 are similar to kaolinite [53], so the ascriptions are often difficult to be recognized, but they still have some distinctive bands. Each vibration line is assigned to the stretching or deformation of the groups and bonds in the samples according to the literature [48,[54][55][56][57]; the FTIR spectra of Hal from different regions are shown in Figure 2 and the ascriptions are included in Table 2, respectively. The double adsorption bands at around 3696 cm −1 and 3620 cm −1 were ascribed to the stretching vibration of the adsorbed water.…”
Section: Ftir Analysismentioning
confidence: 99%
“…This means that the size and shape of particles and clusters play an important role in thermal conductivity enhancement [21][22][23]. Because it was found that materials with chain-like structures, nanofibers or nanotubes have the highest thermal conductivity, much research has been performed on applications of CNTs nanofluids [24][25][26][27], titanium dioxide nanotube [28], titanate nanotube [29], halloysite nanotube nanofluids [30], etc. Venerus et al [31] implemented the benchmark research for the comparison of viscosity values of the same samples from different research groups.…”
Section: Introductionmentioning
confidence: 99%
“…Alberola et al prepared the halloysite nanofluid and improved its stability by setting pH = 12. The studied temperature was from 40 to 80 • C. The thermal conductivity enhancement was 8% at 5% volume concentration and T = 80 • C, while the viscosity increased with halloysite content [30].…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies that utilize the clay minerals for nanofluids applications. For example, Algeria et al [24] studied the stability and thermal properties of halloysite-water nanofluids. They showed that these nanofluids had a lower Prandtl number than conventional nanofluids and could be used in thermal applications.…”
Section: Introductionmentioning
confidence: 99%